2005
DOI: 10.1093/humrep/deh885
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of sperm DNA fragmentation as measured by terminal uridine nick end-labelling assay

Abstract: This longitudinal study shows that sperm DNA fragmentation is a parameter with good stability (repeatability) over time; it can be taken as a baseline both in healthy fertile men and in patients from infertility couples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
3
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 37 publications
4
24
3
4
Order By: Relevance
“…We also found that the variability of sDF was lower than that of any standard semen parameter, and lower than what had been previously reported ($30%) for similar periods with the use of both SCSA (36,37) and TUNEL (38). Such a difference could be due to the recruitment criteria adopted in our study that, at variance with the above studies (36)(37)(38), excluded any conditions among those that so far are known to affect sDF (including recent pharmacologic therapies and fever episodes [28,29]).…”
Section: Figurecontrasting
confidence: 62%
See 1 more Smart Citation
“…We also found that the variability of sDF was lower than that of any standard semen parameter, and lower than what had been previously reported ($30%) for similar periods with the use of both SCSA (36,37) and TUNEL (38). Such a difference could be due to the recruitment criteria adopted in our study that, at variance with the above studies (36)(37)(38), excluded any conditions among those that so far are known to affect sDF (including recent pharmacologic therapies and fever episodes [28,29]).…”
Section: Figurecontrasting
confidence: 62%
“…Such a difference could be due to the recruitment criteria adopted in our study that, at variance with the above studies (36)(37)(38), excluded any conditions among those that so far are known to affect sDF (including recent pharmacologic therapies and fever episodes [28,29]). Indeed, when some of these conditions are excluded, the variability of sDF results decreased ($20% [39]).…”
Section: Figurementioning
confidence: 99%
“…Therefore, it should have a higher predictive value than other tests that measure "potential" DNA damage. This is further supported by recent studies which use the TUNEL assay to determine sperm DNA fragmentation and demonstrate a highly predicative value for male fertility in natural conception with 96.5% sensitivity and 89.4% specificity and good stability [16,36]. The second one is the SCSA, often referred as being able to reflect only "potential" DNA damage.…”
Section: Introductionmentioning
confidence: 63%
“…Standard seminal parameters of sperm concentration, motility, and normal morphology can be highly variable over time within individuals [4,6,82]. In comparison, measures of sperm DNA damage has been shown to have good stability over time within individual with TUNEL [110,111] and SCSA assays [39,127,130]. Earlier studies have reported low coefficients of variation (CV) of 10% [39] and 21 % [127,130] of DFI with the SCSA.…”
Section: Sperm Chromatin Dispersion Testmentioning
confidence: 99%
“…These studies utilized a variety of different assays to analyze sperm DNA integrity but consistently showed that infertile men have a significantly higher level of sperm DNA damage when compared with fertile men. A threshold value of 20% sperm DNA fragmentation with TUNEL assay has been suggested to distinguish between fertile controls and infertile men [110,111]. Additionally, ≥30% or >40% DFI as measured by the SCSA has also been suggested as specific threshold levels, above which the chance of pregnancy approaches zero [40,114].…”
Section: In Vivo Fertilizationmentioning
confidence: 99%